(untitled) (Research, Society and Development, 2022)
The plant Cichorium intybus L., also known as Chicory, is found in different parts of the world and has a rich phytochemical composition. Within its spectrum of action, the plant has been studied about its performance against pathogenic microorganisms and biofilm. Therefore, the objective of the present study is to realize a literature review on the antimicrobial and antibiofilm actions of the species Cichorium intybus. For this, searches were carried out in the databases PubMed / MEDLINE, EMBASE, Gale - Academic OneFile and Science Direct for articles published until August 2020, using the MeSH descriptors “Anti-infective agents“, “Dentistry” and “Periodontal disease” and its derivatives together with the keyword “Cichorium intybus” and its variants. A total of 998 results were found. After a critical reading of titles and abstracts, 18 articles were selected for the preparation of the study. The review includes articles published without time restriction and that approach the species Cichorium intybus with antimicrobial and antibiofilm action. Case reports and literature reviews were excluded. Chicory has a rich variety of chemical compounds that ensure it a wide range of uses, presenting action against bacteria, fungi and viruses, especially the Hepatitis B virus. Therefore, Almeirão has a good antimicrobial and antibiofilm performance in vitro, however, more studies are needed to standardize the study methodology, in addition to elucidating the clinical practice of the plant.